EFFECTIVENESS OF STATE CIVIL APPARATUS PERFORMANCE AT THE NORTH LANGOWAN DISTRICT OFFICE, MINAHASA REGENCY - Kairupan, Sisca B.; Dilapanga, Abdul R.; Iroth, Maria M.L (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2023)
The progress of each agency in carrying out government administration is greatly influenced by Human Resources, namely the State Civil Apparatus because it is part of government management to carry out its main tasks and functions in government. This research aims to find out, describe and analyze the effectiveness of the State Civil Apparatus at the North Langowan District Office, Minahasa Regency. This research uses a descriptive qualitative approach, the number of informants is 5 people with data collection techniques, namely observation, interviews and documentation, with data analysis techniques through data reduction, data presentation and drawing conclusions. Based on research data and information, the effectiveness of ASN performance at the North Langowan District Office is not yet fully effective. The performance targets set for each ASN are in accordance with existing provisions, however in the Performance Assessment the performance results still need to be improved, especially in public services, the factors that influence the effectiveness of ASN performance are work motivation, work environment, leadership, office facilities, resources human beings, ASN who have insufficient abilities or skills will hinder work, inadequate facilities and infrastructure can make work less effective. Therefore, researchers suggest that the performance targets of each ASN remain guided by the applicable rules and regulations, performance appraisals are assessed From the results of their performance, ASNs are required to complete their performance targets and there needs to be supervision from the leadership for ASNs who lack discipline and improve the quality of service to the community. Kemajuan setiap instansi dalam melaksanakan penyelenggaraan pemerintahan sangat dipengaruhi oleh Sumber Daya Manusia yaitu Aparatur Sipil Negara karena merupakan bagian dari manajemen pemerintahan untuk melaksanakan tugas pokok dan fungsinya dalam pemerintahan. Penelitian ini bertujuan untuk mengetahui, mendeskripsikan dan menganalisis bagaimana Efektivitas Aparatur Sipil Negara Kantor Kecamatan Langowan Utara Kabupaten Minahasa. Penelitian ini menggunakan pendekatan kualitatif deskriptif, jumlah informan sebanyak 5 orang dengan teknik pengumpulan data yaitu observasi, wawancara dan dokumentasi, dengan teknik analisis data melalui reduksi data, penyajian data dan penarikan kesimpulan. Berdasarkan data dan informasi penelitian, efektivitas kinerja ASN pada Kantor Kecamatan Langowan Utara belum sepenuhnya efektif. Target kinerja yang ditetapkan untuk setiap ASN sudah sesuai dengan ketentuan yang ada, namun dalam Penilaian Kinerja hasil kinerja masih perlu ditingkatkan terutama dalam pelayanan publik, faktor-faktor yang mempengaruhi efektivitas kinerja ASN yaitu motivasi kerja, lingkungan kerja, kepemimpinan, fasilitas kantor, sumber daya manusia, ASN yang memiliki kemampuan atau skill yang kurang akan menghambat pekerjaan, sarana dan prasarana yang masih kurang dapat membuat pekerjaan menjadi kurang efektif.Oleh karena itu, peneliti menyarankan agar target kinerja setiap ASN tetap berpedoman pada aturan dan ketentuan yang berlaku, penilaian kinerja dinilai dari hasil kinerjanya untuk itu ASN dituntut untuk menyelesaikan apa yang menjadi target kinerjanya dan perlu adanya pengawasan dari pimpinan untuk ASN yang kurang disiplin dan meningkatkan kualitas pelayanan bagi masyarakat.